Maximal Oxygen Consumption Is Reduced in Aquaporin-1 Knockout Mice - Al-Samir, Samer; Goossens, Dominique; Cartron, Jean-Pierre; Nielsen, Søren; Scherbarth, Frank; Steinlechner, Stephan; Gros, Gerolf; Endeward, Volker (Frontiers in Physiology, 2016)
We have measured maximal oxygen consumption (V’O2,max) of mice lacking one or two of the established mouse red-cell CO2 channels AQP1, AQP9 and Rhag. We intended to study whether these proteins, by acting as channels for O2, determine O2 exchange in the lung and in the periphery. We found that V’O2,max as determined by the Helox technique is reduced by 16%, when AQP1 is knocked out, but not when AQP9 or Rhag are lacking. This figure holds for animals respiring normoxic as well as hypoxic gas mixtures. To see whether the reduction of V’O2,max is due to impaired O2 uptake in the lung, we measured carotid arterial O2 saturation (SO2) by pulse oximetry. Neither under normoxic (inspiratory O2 21%) nor under hypoxic conditions (11% O2) is there a difference in SO2 between AQP1null and WT mice, suggesting that AQP1 is not critical for O2 uptake in the lung. The fact that the % reduction of V’O2,max is identical in normoxia and hypoxia indicates moreover that the limitation of V’O2,max is not due to an O2 diffusion problem, neither in the lung nor in the periphery. Instead, it appears likely that AQP1null animals exhibit a reduced V’O2,max due to the reduced wall thickness and muscle mass of the left ventricles of their hearts, as reported previously. We conclude that very likely the properties of the hearts of AQP1 knockout mice cause a reduced maximal cardiac output and thus cause a reduced V’O2,max, which constitutes a new phenotype of these mice.